Higher Prevalence and Age Susceptibility of Intracranial Aneurysm in Patients With Acoustic Neuroma - You, Honghai; Bai, Yue; Yu, Ting; Zeng, Tiefa; Huang, Nan; Mei, Wenzhong; Jiang, Changzhen; Kang, Dezhi; Wu, Xiyue; Chen, Fuxiang (Frontiers in Neurology, 2020)
Introduction: The purpose of this study was to verify whether the prevalence of intracranial aneurysm (IA) in patients with acoustic neuroma is greater than that in age- and sex-matched controls, and to evaluate independent risk factors related to the occurrence of IA. Methods: We retrospectively analyzed 231 patients diagnosed of acoustic neuroma at our institute between 2015 and 2019, and 489 controls from the medical examination center. Cerebrovascular angiography was acquired from all subjects to assess the presence of IA or not. The prevalence of IA, and risk factors associated with a higher IA occurrence were compared, respectively. Results: Cerebral aneurysms were detected in 23 patients (10.0%) and 11 controls (2.2%). The prevalence of IA was significantly different between patients with acoustic neuroma and controls (p < 0.001), and the difference was mainly reflected in the age of 50 and above. In the subgroup analysis, there were distinct differences in several clinical features including age, hypertension, tumor volume and cystic change between patients coexisted with IA or not. However, the age was a unique independent risk factor for coexistence of IA in patients with acoustic neuroma after multivariate logistic regression (OR 1.050, 95%CI 1.008-1.093, p = 0.019). Conclusions: Our results demonstrate that the patients with acoustic neuroma have a higher prevalence of IA than general populations. Older age is correlated with greater occurrence of IA in these patients.